Beyond the Theoretical Impasse: Extending the applications of Transactional Distance Theory - Gokool-Ramdoo, Sushita (International Review of Research in Open and Distributed Learning, 2008)
The premise of this article is that the Transactional Distance Theory (TDT) should be accepted as a global theory for the further development of distance education. Despite the fact that a transactional approach seems to be consciously or unconsciously adopted by theorists and practitioners alike, the reluctance to recognise it as a global theory has plunged distance education into a theoretical impasse from whence there has not been much development. It is argued that the TDT can have applications along all the supply chain of the distance education enterprise: it can explicate and ensure the sustainability of quality distance education in a technology-driven world, and; encapsulate the national concerns for policy development. TDT is seen as a useful instrument that should effectively inform institutional as well as national development.